A diagnosis of knowledge management in a public hospital: A case study of employees' views - Agnieszka Krawczyk-Sołtys (Economic and Environmental Studies (E&ES), 2012)
The aim of this article is to make a diagnosis of the extent in which knowledge management is applied in a public hospital in the Opole region in Poland, based on the empirical research among the hospital's management and employees. The research shows the engagement of the employees in the management of knowledge, as well as their consciousness regarding its importance. The management appears to have similar opinions as the employees. It is argued that the hospital is to a large extent oriented on knowledge management, which is important for its competitive position towards other hospitals.
Keywords: 330; knowledge; hospital; knowledge management; Poland